Prehospital emergency services screening and referral to reduce falls in community-dwelling older adults: a systematic review. Issue 5 (11th January 2016) - Zozula, Alexander; Carpenter, Christopher R; Lipsey, Kim; Stark, Susan
Abstract : Background: Falls represent an increasing source of geriatric morbidity and mortality. Prehospital emergency services may be uniquely suited to screen and refer subsets of high-risk older adults to fall prevention programmes. This systematic review assesses the effectiveness of such screening and referral programmes. Methods: We searched PubMed, Embase, CINAHL, Web of Science, Scopus, the Cochrane Library and OTseeker for English-language peer-reviewed randomised trials, non-randomised trials and cohort studies evaluating prehospital fall risk screening and referral programmes for community-dwelling adults ≥60 years of age. Risk of bias was assessed using the Cochrane Collaboration's tool. Primary outcomes included the risk and rate of falling. Secondary outcomes included successful follow-up to address fall risks and adverse events. Results: From 6187 unique records, 6 studies were included. Screening varied from using semistructured risk assessments to recording chief complaints. All studies were at high risk of bias. One unblinded trial of a multifactorial fall prevention programme demonstrated a 14.3% (95% CI 6.1% to 22.5%) absolute reduction in annual fall risk and a relative fall incidence of 0.45 (95% CI 0.35 to 0.58). The probability of successful follow-up varied from 9.8% to 81.0%. No studies demonstrated any attributable adverse events. Conclusions: No high-quality evidence demonstrates that prehospital services reduce falls in community-dwelling older adults. Screening by prehospital personnel using semistructured risk assessments appears feasible, but it is unclear whether this is superior to referral based on fall-related chief complaints. Trial registration number: PROSPERO 2012:CRD42012002782.